Analysis of Causality Interactions Between Education, Inequality, and Unemployment Toward Poverty in East Java: Empirical Evidence from Dynamic Panel Co-integration Model - Indrawan Firdauzi; Ni Made Ratih Kusuma Dewi (Universitas Muhammadiyah Yogyakarta, 2022)
The issue of poverty has been faced for a long time. In Indonesia today, East Java is the most significant contributor to the poor people. With various policies that the government has implemented, the issue of poverty remains unsolved. This study, therefore, discusses the causality relationship between education, inequality, and unemployment toward poverty in East Java. Using secondary data from the Central Statistics Agency of Indonesia (BPS), we estimated dynamic panel data of cities and regencies in East Java from 2012 to 2017. Employing the Granger causality approach, it was found that education has a one-way relationship with inequality and a two-way relationship with unemployment. In addition, poverty has a one-way relationship with all the variables used. In the long term, education has a negative correlation with poverty. According to our findings, both the government and the private sector need to expand more job opportunities and improve education for the poor as both sectors significantly reduce poverty in the long term.